Determinant of Zakat Productive towards Small Medium Enterprise (SMEs) Incomes of Recipient of Zakat - Ichsan Hamidi Hamidi; Suhel Dirta Pratama Atiyatna Atiyatna; Alghifari Mahdi Igamo Igamo (Islamic Economics Journal, 2021)
This study aims to find out the determinant of zakat productive towards Small Medium Enterprise (SMEs) incomes of recipient of zakat. This study uses quantitative approaches using primary data which collect through interviews, documentation and observation with a quetionnaire. The population are all recipients of zakat who received the funding of zakat productive from BAZNAS of South Sumatera. The data is analyzed using multiple reggression model. The results of this study indicate that the determinant of zakat productive like zakat productive funds and training has a significant contribution on SMEs incomes of recipient of zakat. On this point zakat productive program can be developed more broadly and with more scheme, so that more recipients of zakat can join this program and got more welfare and a good living.